2006
DOI: 10.1002/anie.200602211
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Faces of Halogenated Marine Natural Products: Total Synthesis of the Reported Structures of Elatenyne and an Enyne from Laurencia majuscula

Abstract: Knocking them into shape: The total synthesis of two reported marine natural products containing halogenated pyrano[3,2‐b]pyrans (see example in blue) has led to the reassignment of both structures as halogenated 2,2′‐bifuranyls (red). Concomitantly an efficient route to pyrano[3,2‐b]pyrans is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…Several cases of an exocyclic olefin on a 5-membered ring as opposed to a 6-membered ring with endocyclic bond are evident in Table 1, for example, chloroaurone, 10, 11 aspergiones A and B, 1214 pyrostatins A and B, 15, 16 and spongotine B. 17, 18 Another problematic theme is differentiation of fused 6-membered rings from two 5-membered rings linked by a single bond, as seen in the examples of the red algal metabolites laurendecumenyne B, 19, 20 elatenyne 21, 22 and Laurencia enyne. 22, 23 In these three compounds, the observed 13 C NMR shifts of the oxygen-bearing carbons were more consistent with a 2,2′-bifuranyl moiety (> 76 ppm) than the proposed pyrano[3,2- b ]pyran (< 76 ppm).…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…Several cases of an exocyclic olefin on a 5-membered ring as opposed to a 6-membered ring with endocyclic bond are evident in Table 1, for example, chloroaurone, 10, 11 aspergiones A and B, 1214 pyrostatins A and B, 15, 16 and spongotine B. 17, 18 Another problematic theme is differentiation of fused 6-membered rings from two 5-membered rings linked by a single bond, as seen in the examples of the red algal metabolites laurendecumenyne B, 19, 20 elatenyne 21, 22 and Laurencia enyne. 22, 23 In these three compounds, the observed 13 C NMR shifts of the oxygen-bearing carbons were more consistent with a 2,2′-bifuranyl moiety (> 76 ppm) than the proposed pyrano[3,2- b ]pyran (< 76 ppm).…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…In this work, an insufficient amount of the compound has been isolated to provide a good quality crystal for an X-ray, and the assignment was based on NMR data. However, in contrast to [2,2′]bifuranyl-pyranopyran models [41], the 13 C chemical shifts of the ring fusion atoms in 13a and 13b do not provide the distinction of the ring size [42]. Based on the literature evidence of compound 13a being the major isomer in solution [43], we propose the structure of the induced natural product to be 5a,6,11a,12-tetrahydro-5a,11a-dimethyl[1,4]benzoxazino[3,2- b ][1,4]benzoxazine ( 13a ).…”
Section: Resultsmentioning
confidence: 99%
“…For two decades, the structure of elatenyne remained unchallenged, until Burton and co-workers 57 revised it by total synthesis. As depicted in Scheme 11, one of the key steps in their synthetic approach was the generation of the pyrano[3,2-b]pyran system 96 from the thermodynamically favored rearrangement of the corresponding 2,2'-bifuranyl compound 95a.…”
Section: Elatenynementioning
confidence: 99%
“…However, they could not unequivocally determine the relative configuration of the natural product. 57 To settle this issue, Burton and co-workers established a collaboration with Goodman and co-workers to computationally unravel the most likely tridimensional structure of elatenyne. 58 From NMR calculations at the affordable B3LYP/6-31G**//MMFF level of theory, in one of the most exquisitely discussed papers in the pre-DP4 era, the authors compared the correlation coefficients and the averaged and maximum errors computed for the 32 possible diastereoisomers (including different approaches to deal with the large errors computed for the bromine- containing carbons) and concluded that structure 99 was the most likely candidate (Figure 23).…”
Section: Elatenynementioning
confidence: 99%
See 1 more Smart Citation